Breaking through establishing football through a professional league in the United States and the Philippines - Baquiran, Joshua Hans B. (2014)
The popularity of football across various continents and nations has allowed it to be distinguished as the “world’s game.” However, in countries like the United States and the Philippines, football has failed to be recognized as a major spectator sport. The creation of professional leagues, such as the North American Soccer League (1968–1984) and the United Football League (2009–present), is clearly an attempt to popularize the sport in countries that have previously shown little interest. Beginning with a brief historical overview of the events that shaped the creation and legacy of both leagues, this research note shall aim to identify key similarities and differences between both leagues and highlight how these have affected the emergence of football as a major spectator sport within these societies.
Keywords: Soccer